2021
DOI: 10.1093/nsr/nwab174
|View full text |Cite
|
Sign up to set email alerts
|

Massive lithospheric delamination in southeastern Tibet facilitating continental extrusion

Abstract: Significant left-lateral movement along the Ailao Shan-Red River fault accommodated a substantial amount of the late Eocene to early Miocene India-Asia convergence. However, the activation of this critical strike-slip fault remains poorly understood. Here, we show key seismic evidence for the occurrence of massive lithospheric delamination in southeastern Tibet. Our novel observation of reflected body waves (e.g. P410P and P660P) retrieved from ambient noise interferometry sheds new light on the massive founde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Horizontally underthrusting Indian continental lithosphere directly underlies Tibetan crust and Tibetan lithospheric mantle must thus have delaminated prior to the 25-Ma onset of horizontal underthrusting in western and eastern Tibet. In addition, not only the source area below the Tibetan Plateau, but also the ‘sink’ of Middle Miocene and younger crustal motion in the Yunnan region has undergone lithospheric delamination [ 47 ]. This suggests that the onset of E–W extension 15–10 Ma was likely not triggered by delamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontally underthrusting Indian continental lithosphere directly underlies Tibetan crust and Tibetan lithospheric mantle must thus have delaminated prior to the 25-Ma onset of horizontal underthrusting in western and eastern Tibet. In addition, not only the source area below the Tibetan Plateau, but also the ‘sink’ of Middle Miocene and younger crustal motion in the Yunnan region has undergone lithospheric delamination [ 47 ]. This suggests that the onset of E–W extension 15–10 Ma was likely not triggered by delamination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, seismic tomographic evidence for bodies of high-velocity material that may represent delaminated Tibetan lithosphere have been identified in the upper mantle below the horizontally underthrust Indian lithosphere, suggesting delamination prior to underthrusting [ 46 ]. Moreover, recent seismological analysis has shown that delamination is not restricted to Tibet, but also affected the Yunnan region to the southeast of the eastern Himalayan syntaxis, where a conspicuous, circular-shaped hole in the continental lithosphere is underlain by a body of high-velocity material at the base of the upper mantle [ 47 ].…”
Section: Reviewmentioning
confidence: 99%
“…Receiver function results (Hu et al, 2012;Yang et al, 2017) suggest that the lithospheric thickness has significantly thinned (<100 km) in the Indochina Block and Cathaysia Block. Lithospheric thinning may be caused by lithospheric delamination (Chung et al, 1997;Feng et al, 2022) and rollback of the Indian Plate (Li et al, 2008;Lei and Zhao, 2016;Huang et al, 2019). Then, asthenospheric upwelling and dehydration of the subducting plate caused the large-scale lowvelocity anomaly in this area.…”
Section: The Deformation Mechanism In the Upper Mantlementioning
confidence: 99%
“…The heating source of partial melting is from asthenospheric upwelling linked to breakoff and roll back of the subducting Neo‐Tethys oceanic lithosphere (Hou et al., 2012; Ji et al., 2016; Kapp & DeCelles, 2019). Geochronology, topographic modeling, and seismic data have been used to argue for massive lithospheric delamination in southeastern Tibet from 40 to 30 Ma (Feng et al., 2022; Xiong et al., 2022). Geochronology from the Mabja dome constrains the timing of peak metamorphism, and onset of mid‐crustal ductile extension to ca.…”
Section: Discussionmentioning
confidence: 99%